Performance evaluation of HIV infection diagnostic tests - Márcia Jorge Castejon; Rosemeire Yamashiro; Carmem Aparecida F Oliveira; Evelyn Helena A Mata; Luís Fernando M Brígido; Mark Drew C Guimarães; Maria Amélia S. M Veras (Sociedade Brasileira de Patologia Clínica, 2020)
ABSTRACT Introduction: Many factors can impact the performance of diagnostic assays for the human immunodeficiency virus (HIV) infection, affecting the results of population surveys. Objective: The objective of this study was to evaluate the performance of point-of-care rapid tests (RT) used for HIV diagnosis as compared to conventional tests in blood samples from a population of transvestites and transsexual women. Methods: A total of 1,385 samples with HIV RT results were submitted to Instituto Adolfo Lutz for evaluation by conventional laboratory tests. Results: HIV positivity was confirmed by conventional laboratory tests in 100% of the 240 (17.3%) samples with reactive RT. However, 1,145 (82.7%) samples with non-reactive RT results were evaluated; three (0.3%) tested positive and one (0.1%), indeterminate for HIV. Although a proportion of discordant results were found, the point-of-care RTs showed a high confirmation rate when compared to the serological tests. Conclusion: The data of this study corroborate the importance of adopting effective management tools to ensure quality of HIV infection diagnosis.